2019
DOI: 10.1111/1556-4029.14198
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Background Levels of Male DNA on Underpants Worn by Females

Abstract: This study is the first to examine the background level of male DNA on underpants worn by females in the absence of sexual contact. Here, we examined 103 samples from the inside front of underpants from 85 female volunteers. Samples were examined for the presence of male DNA using NGM SElect and PowerPlex Y23 kits. Only five samples gave a “complete” Y‐STR profile, even though 83.5% of our volunteers cohabited with a male. In all cases where a partner reference sample was available, the Y‐STR profile matched t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…examines background levels of body fluids and DNA on the shaft of the penis and associated underpants in the absence of sexual activity, while Murphy et al. provide a large dataset of background male DNA on the inside front of female underwear [25, 26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…examines background levels of body fluids and DNA on the shaft of the penis and associated underpants in the absence of sexual activity, while Murphy et al. provide a large dataset of background male DNA on the inside front of female underwear [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…As with Case 1, a pre-case assessment was carried out based on this background information, which set out the issue that can be addressed (whether or not sexual intercourse occurred), competing propositions (Hp-sex occurred, Hd-no sex occurred, both parties were socializing at the house party) and expectations of possible outcomes (based on these competing propositions). The probabilities of possible findings, given the competing propositions (Hp and Hd), were assigned based on published work [4,5,25].…”
Section: Casementioning
confidence: 99%
“…Studies have also considered the level of DNA an individual transfers to untouched items in their immediate surroundings [ 328 ], the position and level of DNA transferred during digital sexual assault [ 329 ] or during various activities with worn upper garments [ 330 , 331 ], and the DNA composition on the surface of evidence bags pre- and post-exhibit examination [ 332 ]. Studies assessing background levels of male DNA on underpants worn by females [ 333 ] and background levels of DNA on flooring within houses [ 334 ] are providing important knowledge about the possibilities and probabilities of DNA transfer and persistence.…”
Section: Advancements In Current Practicesmentioning
confidence: 99%
“…A further study by Murphy et al [145] examined the background levels of male DNA on the inside front of clean, but not new, pairs of underpants worn for a day by a female who was asked to abstain from sexual intercourse for 48 h prior to taking part in the study. The authors reported that, of the 103 samples taken after a day of wearing, 83 showed the presence of male DNA to varying quantities (as detected by the Quantifiler Trio DNA quantification kit (Thermo Fisher Scientific, Warrington, UK)) and 24 contained sufficient DNA to proceed to profiling.…”
Section: Prevalence and Backgroundmentioning
confidence: 99%